3D Electronic Game Research and Development for Christians (Research, Society and Development, 2018)
With the technological growth in relation to the electronic games, the debates on the subject also increased, because some young people exaggerate and spend hours and hours in frete to electronic devices. For the evangelical environment, this fact does not seem pleasant, since it can become a problem because, according to literature, it leads them to have different and even aggressive behavior and attitudes in the social context. When doing the research on the subject it was possible to realize that the area of games aimed at Christians does not grow in the same proportion as others, and with that they do not have an entertainment medium specifically aimed at their profile. This article aims to present the development of a 3D electronic game aimed at young Christians in order to introduce and increase the interest of the end user. For this we used the game engine Unity for development of the project and Sketchup for modeling the 3D objects of the scenarios